Design automation of RF IC layout - Zhan, Peng (2013)
This report is presented by the design automation of radio frequency (RF) integrated circuit layout of Inductors/transformers. The objective of this layout automation generation is to promote user in quickly and automatically generating their design layout and at the same time, enhance the RF design and simulation capabilities of the Cadence software. The Cadence SKILL is a interactive programming language which used in this project to design the layout of planar inductors. This will shorter the time needed to layout inductors with (design rule specification) and different matching can result better performance, if more precise, in this competitive RF design industry.